Odpowiedzi

Najlepsza Odpowiedź!
2010-03-16T12:07:15+01:00
Dla a = 2, b = 0,5

3a + 3a-b + 13a-7b + 3a + 2b + 2a = 24a -6b
24 * 2 -6 * 0,5 = 48 - 3 = 45

2a + 3b-a + 2a + 3b-a + 3b-a = a +9b
2 + 9 * 0,5= 2 + 4,5 = 6,5

3b + b + 2a-b + b + a-b =3b + 3a
3*0,5 + 3 * 2 = 1,5 + 6 = 7,5
2 3 2
2010-03-16T12:11:10+01:00
A)
3a + 3a-b + 13a-7b + 3a + 2b + 2a =24a-6b
24*2-6*0,5=48-3=45

b)
2a + 3b-a + 2a + 3b-a + 3b-a =a+9b
1*2+9*0,5=2+4,5=6,5

c)
3b + b + 2a-b + b + a-b =3b+3a
3*0,5+3*2=1,5+6=7,5
:P
2 4 2
2010-03-16T12:23:44+01:00
3a+3a-b+13a-7b+3a+2b+2a=24a-6b
Ob. 24*2-6*0,5=48-3=45
2a+3b-a+2a+3b-a+3b-a=a+9b
Ob. 2+9*0,5=2+4,5=6,5
3b+b+2a-b+b+a-b=3b+3a
Ob. 3*0,5+3*2=1,5+6=7,5
1 1 1